Practice Recommendations for Transcranial Doppler Ultrasonography in Critically Ill Children in the Pediatric Intensive Care Unit: A Multidisciplinary Expert Consensus Statement - O'Brien, Nicole Fortier; Reuter-Rice, Karin; Wainwright, Mark S.; Kaplan, Summer L.; Appavu, Brian; Erklauer, Jennifer C.; Ghosh, Suman; Kirschen, Matthew; Kozak, Brandi; Lidsky, Karen; Lovett, Marlina Elizabeth; Mehollin-Ray, Amy R.; Miles, Darryl K.; Press, Craig A.; Simon, Dennis W.; Tasker, Robert C.; LaRovere, Kerri Lynn (Journal of Pediatric Intensive Care, 2020)
Transcranial Doppler ultrasonography (TCD) is being used in many pediatric intensive care units (PICUs) to aid in the diagnosis and monitoring of children with known or suspected pathophysiological changes to cerebral hemodynamics. Standardized approaches to scanning protocols, interpretation, and documentation of TCD examinations in this setting are lacking. A panel of multidisciplinary clinicians with expertise in the use of TCD in the PICU undertook a three-round modified Delphi process to reach unanimous agreement on 34 statements and then create practice recommendations for TCD use in the PICU. Use of these recommendations will help to ensure that high quality TCD images are captured, interpreted, and reported using standard nomenclature. Furthermore, use will aid in ensuring reproducible and meaningful study results between TCD practitioners and across PICUs.
Keywords: transcranial doppler ultrasound; pediatric critical care; practice recommendations; protocol; pediatric intensive care unit